Digitally programmable current amplifier - Prasertsom, Danucha; Photsathian, Thongchai; Tangsrirat, Worapong (My University, 2012)
In this paper, a the digitally programmable current amplifier (DP-CA) for NMOS integrated circuit implementation is presented. To provide precise digital control of the gain characteristic, the proposed DP-CA comprises current proportional gain blocks that can be digitally controlled. The proposed DP-CA can be operated from a low power supply of ±1.25V. As an application example of the proposed circuit, the digitally programmable current-mode first-order allpass filter is described. Simulation results using 0.35-μm TSMC CMOS process parameters are also included. © 2012 IEEE.
Keywords: allpass filter; current amplfier; digitally programmable; NMOS transistor